ASSOCIATION RULE METHOD FOR INFORMATION SYSTEM EPIDEMIC DENGUE MAPPING BASED ASSOCIATION OF RISK FACTORS IN PALEMBANG - Ermatita Ermatita; Suci Destriatania (Proceeding International Conference on Information Technology and Business, 2015)
Endemic diseases dangerous such as dengue fever must be handling seriously for the risk minimize by the disease. Dengue Hemorrhagic Fever (DHF) is disease has not been found vaccine or cure is powerful. It is necessary treatment to prevent the occurrence of dengue fever, especially when it came to the incidence of dengue fever endemic in certain areas by doing Epidemiologist dengue fever. Epidemiology is identification of risk factors for DHF to find level of area risk. Risk factors of hemorrhagic fever endemic must be identified to prevent the occurrence of dengue fever. Identifying risk factors and risk factors association can potential increase the occurrence of dengue fever. This study developed mapping information system Dengue epidemic through Association rule method of data mining. The information generated in the map of epidemic DHF level based association of potential risk factors that cause hemorrhagic fever endemic. Analysis with the Association Rule to determine level of DHF epidemic area based data reporting system. KEY WORDS: information system mapping, data mining, Association Rule, endemic, Dengue Hemorrhagic Fever (DHF).